A priori revisability in science - Grozdanoff, Boris D. (Cambridge Scholars Publishing, 2014)
The most influential rationalist model of scientific knowledge is arguably the one formulated recently by Michael Friedman. The central epistemic claim of the model concerns the character of its fundamental principles which are said to be independent from experience. Friedman's position faces the modern empiricist challenge: he has to explain how the principles could still be a priori if they change under empirical pressure. This book provides a contemporary account of the epistemic character ...